Menerapkan Model Reading Guide Berbasis Paikem dalam Upaya Meningkatkan Motivasi Belajar Peserta Didik Kelas VI SD Negeri 27 Ampenan - Nurmala, Siti (Jurnal Paedagogy, 2020)
This study aims to determine the effectiveness of the application of the PAIKEM-based Reading Guide model in an effort to improve the learning activities of Grade VI Students of SD Negeri 27 Ampenan. This research method uses classroom action research conducted in two cycles, each cycle of activities is; planning, implementation, observation and reflection. The final results of the action in the second cycle showed that the results of teacher observation obtained an average score (4.79) and the results of student observations achieved an average score (4.17). While the results of increased student learning motivation is an increase in student learning outcomes reaching an average value (78.77), meaning that the indicators of success (> 70.00) have been exceeded. Because the indicators of success have been proven, this study was declared successful and the study was stopped in the second cycle.